Bidirectional Longitudinal Relations Between Parent–Grandparent Co-parenting Relationships and Chinese Children’s Effortful Control During Early Childhood - Li, Xiaowei; Zhou, Siyu; Guo, Yuanfang (Frontiers in Psychology, 2020)
Parent–grandparent co-parenting has become a common mode in Chinese families; however, its correlation with children’s development in the long run remains unclear. Herein, a 10-month follow-up survey was conducted among 253 preschool children and their parents from Chinese parent–grandparent co-parenting families. It aimed to examine the bidirectional longitudinal correlation of children’s effortful control with mother–grandparent and father–grandparent co-parenting relationships, as well as the dissimilarity of the two co-parenting relationships. In addition, the moderating role of maternal parenting self-efficacy in these relationships was also investigated. A cross-lagged model showed that the (1) mother–grandparent co-parenting relationship (T1) positively predicted the father–grandparent co-parenting relationship (T2), (2) dissimilarity of the mother–grandparent and father–grandparent co-parenting relationships (T1) negatively predicted children’s effortful control (T2), and (3) maternal parenting self-efficacy significantly moderated the predictive effect of children’s effortful control on a father–grandparent co-parenting relationship. However, a further simple slope analysis showed that after controlling the father–grandparent co-parenting relationship (T1), the children’s effortful control (T1) did not significantly predict the father–grandparent co-parenting relationship (T2) either in the high or low maternal parenting self-efficacy group. These results indicated that in Chinese parent–grandparent co-parenting families, the father-grandparent co-parenting relationship was influenced by the mother–grandparent co-parenting relationship, and similar mother–grandparent and father–grandparent co-parenting relationships were conducive to the development of the children’s effortful control.